2018
DOI: 10.11648/j.urp.20180302.13
|View full text |Cite
|
Sign up to set email alerts
|

Planning Green Space for Climate Change Adaptation and Mitigation: A Review of Green Space in the Central City of Beijing

Abstract: The ongoing rapid urbanization and its socio-economic impacts on Chinese cities have engendered numerous environmental issues, food insecurity and significant stress on water resources besides accelerating some ecological degradation. Among these issues, urban-heat-island (UHI) and climate change in large cities had drawn much attention so that many researches on climate change adaptation and mitigation emerged in recent years. How to make the cities cool down and more liveable is more important than before fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
6
0
2
Order By: Relevance
“…This result was consistent with the changes and response of green spaces in Beijing in previous studies [67]- [70]. Recent research has indicated that Beijing has implemented the green-wedge initiative to increase the vegetation canopy, and it has achieved remarkable results [69]. The area ratio and growth rate of green spaces increased significantly in the central area of Beijing between 2014 and 2020 [67], [68].…”
Section: B Comprehensive Analysis Of the Rsei And Ecological Indicatorssupporting
confidence: 89%
See 1 more Smart Citation
“…This result was consistent with the changes and response of green spaces in Beijing in previous studies [67]- [70]. Recent research has indicated that Beijing has implemented the green-wedge initiative to increase the vegetation canopy, and it has achieved remarkable results [69]. The area ratio and growth rate of green spaces increased significantly in the central area of Beijing between 2014 and 2020 [67], [68].…”
Section: B Comprehensive Analysis Of the Rsei And Ecological Indicatorssupporting
confidence: 89%
“…Regarding the spatial distributions, the areas with poor and bad EEQ were mainly distributed in the surrounding areas, where environmental management was relatively lacking [68]. The EEQ of central Beijing was higher due to frequent human intervention (e.g., the green-wedge initiative) [67], [69]. Of concern is that the areas where EEQ was improved by 2020 were mainly in the surrounding area of Beijing.…”
Section: B Comprehensive Analysis Of the Rsei And Ecological Indicatorsmentioning
confidence: 99%
“…An additional constraint is that large regions of the Global South are prone to periodic or frequent droughts leading to a decrease in green spaces or quality recreational areas. These trends have been discussed by Dobbs et al (2018) in Santiago, Islam and Tuli (2017) in Bangladesh, and Li et al (2018) by the physiography of the city and its socioeconomics and enlarging the inequity effect. According to Roy et al (2018), people recognise the decline in the availability of trees and green infrastructure, and consequently, their experiences are affected by any decline in the quantity and quality of ecosystem service provision.…”
Section: Inequities In Cultural Ecosystem Servicesmentioning
confidence: 99%
“…Ini terjadi karena RTH mempunyai manfaat multidimensi, diantaranya manfaat lingkungan, manfaat sosial dan manfaat ekonomi. Luas RTH yang ideal cenderung akan mempengaruhi penduduk secara positif (Li et al 2018;Sahni dan Aulakh 2014). RTH juga berpengaruh terhadap pola hidup sehat penduduk terutama yang ada disekitarnya (Lestan et al 2014) Tahun sehingga menjadikan RTH sebagai tempat dimana bermain, rekreasi dan menikmati udara segar (Holt et al 2008).…”
Section: Kebutuhan Rth Kota Jambi Berdasarkan Jumlah Pendudukunclassified